Maternal habitat use of Juniperus excelsa woodland by Pallas's cat Otocolobus manul in Iran. Issue 4 (2nd October 2018) - Dibadj, Parham; Jafari, Behrouz; Nejat, Farshad; Qashqaei, Ali Turk; Ross, Steven
ABSTRACT: Pallas's cat is a rare felid that has a wide but patchy distribution across Eurasia's cold steppes. The species is known to prefer rocky, mountain and shrub steppe habitats, and strongly selects habitats with good cover from sympatric predators, particularly when raising young. This is the first report of the species using Juniperus excelsa woodland habitat for foraging and breeding in Iran. We observed the use of two aged juniper tree cavities as breeding dens for a litter of four kittens. The record extends our capacity to assess the range of habitats that are used and suitable for Pallas's cat populations.